2022
DOI: 10.7759/cureus.26111
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibody (ANCA)-Associated Renal Vasculitis After COVID-19 Infection: A Case Report

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a class of autoimmune diseases that can cause kidney failure because of mononuclear cell infiltration and the destruction of small and mediumsized blood vessels. Coronavirus disease 2019 (COVID-19) may trigger or exacerbate autoimmune diseases. We present a case of ANCA-associated vasculitis in a patient with rheumatoid arthritis after a COVID-19 infection, who presented with intermittent hemoptysis and dyspnea and was diagnosed with COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The incidence of ANCA-associated vasculitis was increased in individuals with COVID-19, which was consistent with previous reports. 48 , 49 , 50 Plausible mechanisms involve viral-induced hypercoagulability resulting from endothelial infection or injury, complement system activation, and dysregulation of the coagulation cascade, ultimately leading to vasculopathy. 51 , 52 Moreover, the protracted exposure of neutrophil extracellular traps has been postulated to elicit the development of antineutrophil antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ANCA-associated vasculitis was increased in individuals with COVID-19, which was consistent with previous reports. 48 , 49 , 50 Plausible mechanisms involve viral-induced hypercoagulability resulting from endothelial infection or injury, complement system activation, and dysregulation of the coagulation cascade, ultimately leading to vasculopathy. 51 , 52 Moreover, the protracted exposure of neutrophil extracellular traps has been postulated to elicit the development of antineutrophil antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we found eight cases of newonset AAV temporally associated with COVID-19 in adults (Table 1). 2,[8][9][10][11][12] After inclusion of the present case, out of the nine patients, five (55%) were female and the mean age was 49.77 years. One (11%) patient had scleroderma, and one (11%) patient had rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors note that COVID-19 and AAVs are multisystem diseases. A causal relationship is believed to exist between the two conditions, and this is supported by clinical case reports [12,22,25,27,29,35,39]. Moreover, the symptoms of COVID-19 can mimic those of vasculitis, especially if the respiratory system is affected.…”
Section: Presentation Of Clinical Cases Casementioning
confidence: 91%
“…Today, there is more and more evidence that SARS-CoV-2 is another virus that can lead to disruption of the regulation of the immune system and provoke the appearance or exacerbate already existing autoimmune diseases in children and adults [24][25][26][31][32][33][34][35], especially in genetically predisposed individuals [12,32,35]. Moreover, numerous new autoimmune diseases in adults have been described in the literature as post-infectious complication of COVID-19 infection [25].…”
Section: Presentation Of Clinical Cases Casementioning
confidence: 99%